Intraoperative magnetic resonance imaging for neurosurgery – An anaesthesiologist's challenge - Gandhe, Rajashree U (Indian J Anaesth, 2018)
Intraoperative magnetic resonance imaging (MRI)-guided neurosurgery has gained popularity over the years globally. These surgeries require a dedicated operating room and MRI-compatible anaesthesia equipment. The anaesthesiologist providing care in this setup needs to be experienced and vigilant to ensure patient safety. Strict adherence to MRI safety checklists and regular personnel training would avoid potential accidents and life-threatening emergencies. Teamwork, good communication, preprocedure planning, and familiarity with the surroundings are very important for safe care and good outcomes. We performed a literature search in Google Scholar, PubMed and Cochrane databases for original and reviewed articles for the origins, development and applications of intraoperative MRI in neurosurgical procedures. Much of the research has emphasised on the surgical indications than the anaesthetic challenges faced during intraoperative MRI guided surgery. The purpose of this review is to discuss the anaesthetic concerns specific to this unique environment.